Saving and Investment: Definitions, Assumptions, Objectives - Lerner, A. P. (Quarterly Journal of Economics, 1939)
Journal Article Saving and Investment: Definitions, Assumptions, Objectives Get access A. P. Lerner A. P. Lerner Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 53, Issue 4, August 1939, Pages 611–619, https://doi.org/10.2307/1883280 Published: 01 August 1939